Examining the Utility of the HIV Disability Questionnaire (HDQ) in Clinical Practice: Perspectives of People Living with HIV and Healthcare Providers. (February 2022) - Vader, Kyle; Chan Carusone, Soo; Aubry, Rachel; Ahluwalia, Puja; Murray, Carolann; Baxter, Larry; Robinson, Gregory; Ibáñez-Carrasco, Francisco; Stewart, Ann; Solomon, Patricia; O'Brien, Kelly K.
Our aim was to examine the utility of the HIV Disability Questionnaire (HDQ), a patient-reported outcome measure for use in clinical practice from the perspectives of people living with HIV (PLWH) and healthcare providers. We conducted a qualitative descriptive study. Fifteen PLWH and five healthcare providers participated in an interview, of which ten PLWH participated in a follow-up focus group discussion. The HDQ has value in clinical practice, including its role in assessing disability, facilitating communication, tailoring treatments, and guiding referrals. Strengths of the HDQ included its comprehensiveness, relevance of domains, and importance of specific items. Concerns related to length of the HDQ, the potential for some items to trigger emotional response, and negative connotations with the term 'disability.' Recommendations for HDQ implementation included the importance of score interpretability, shortening the questionnaire, and tailoring administration to the individual. Results suggest the HDQ possesses clinical utility with PLWH and healthcare providers.